Au Wire Ball Welding and Its Reliability Test for High-Temperature Environment - Chenyang Wu; Junqiang Wang; Xiaofei Liu; Mengwei Li; Zehua Zhu; Yue Qi (Micromachines, 2022)
The long-term application of sensors in a high-temperature environment needs to address several challenges, such as stability at high temperatures for a long time, better wiring interconnection of sensors, and reliable and steady connection of the sensor and its external equipment. In order to systematically investigate the reliability of thin coatings at high temperatures for a long time, Au and Cr layers were deposited on silicon substrates by magnetron sputtering. Additionally, samples with different electrode thicknesses were annealed at different temperatures for a varied duration to study the effect of electrode thickness, temperature, and duration on the reliability of samples. The results of tensile and probe tests before and after heat treatment revealed that the mechanical strength and electrical properties have changed after annealing. In addition, the bonding interface was analyzed by a cross-sectional electron microscope. The analysis showed that long-term continuous high-temperature exposure would result in thinning of the electrode, formation of pores, recrystallization, and grain growth, all of which can affect the mechanical strength and electrical properties. In addition, it was observed that increasing the thickness of the gold layer will improve reliability, and the test results show that although the thin metal layer sample is in poor condition, it is still usable. The present study provides theoretical support for the application of thin coatings in high temperatures and harsh environments.